Dur Labeur Des Femmes Bayam-Sellam Dans L’approvisionnement Des Marchés De La Ville De Douala (Cameroun) En Banane Plantain - Chadji Rosine; Folefack Denis Pompidou (European Scientific Journal, ESJ, 2018)
The main aim of this study is to evaluate the working conditions of some women who supply plantain bananas to markets in Douala. Surveys were conducted among 60 women along National Road 5. This study revealed that the supply chain is dominated by older women (47 years old). Nearly half were married contrary to what one might have thought. Furthermore majority of these women were from the Western Region (76%) and were more experience; to carry out this activity Nevertheless they were faced with difficulties such as Long working hours from 4 am to midnight (than 15 hours) s, braving the risk of aggression and accidents. Their goods were best transported by bus or trucks to the rural markets. In order to purchase this product they are subjected to a lot of challenges and in addition to this, their physical condition must be in order. Another challenge faced by these women is the long waiting hours for trucks or buses to come by. This can take 2–6 hours before the buses arrive. In addition, the activity is mostly appreciated by the actors who do contribute to the economic empowerment of women, because it is profitable. However, they are faced with several constraints such as: theft, insecurity; high cost of transportation; lack of information; poor road infrastructure; police harassment; difficulties to have a warehouse to facilitate the storage and conservation conditions, etc. Due to these constraints, the commercial potential of women is hindered and much lower than it could be.